2020
DOI: 10.3389/fbioe.2020.00259
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Exosome-Derived miR-486-5p Regulates Cell Cycle, Proliferation and Metastasis in Lung Adenocarcinoma via Targeting NEK2

Abstract: Objective: This study aimed to describe the mechanism of exosome-derived miR-486-5p underlying the cell cycle and progression in lung adenocarcinoma (LUAD). Methods: Bioinformatics methods were applied for identifying the differentially expressed genes (DEGs) in the GEO-LUAD dataset, predicting where the potential target miRNA was expressed and exploring the corresponding downstream target mRNA. qRT-PCR was conducted to detect the levels of the target genes in cancer cells. Thereafter, a series of in vitro exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…We recently showed that miR-206 is transferred by satellite cell EVs to fibrogenic cells during MOV to regulate collagen deposition, 7 and confirm here that miR-206 is the most abundant miRNA in MPC EVs ( Figure 2C ). Expanding on our earlier work, we found numerous miRNAs enriched in MPC EVs ( Figure 2C ) that are experimentally shown to lower Mmp9 expression, such as miR-24, 47–49 miR-149, 50–55 and miR-486, 56 , 57 as well as miRNAs that are validated to target the 3′-UTR of Mmp9 mRNA and reduce transcript levels, including Let-7e, 58 miR-133a and -133b, 59 , 60 and miR-320 61 ( Figure 2D ). In silico predicted miRNA-mRNA target analysis 62 further revealed that ECM remodeling is the most regulated process by MPC EV miRNAs ( Figure 2E , Tables S2 and S3 ).…”
Section: Resultssupporting
confidence: 69%
“…We recently showed that miR-206 is transferred by satellite cell EVs to fibrogenic cells during MOV to regulate collagen deposition, 7 and confirm here that miR-206 is the most abundant miRNA in MPC EVs ( Figure 2C ). Expanding on our earlier work, we found numerous miRNAs enriched in MPC EVs ( Figure 2C ) that are experimentally shown to lower Mmp9 expression, such as miR-24, 47–49 miR-149, 50–55 and miR-486, 56 , 57 as well as miRNAs that are validated to target the 3′-UTR of Mmp9 mRNA and reduce transcript levels, including Let-7e, 58 miR-133a and -133b, 59 , 60 and miR-320 61 ( Figure 2D ). In silico predicted miRNA-mRNA target analysis 62 further revealed that ECM remodeling is the most regulated process by MPC EV miRNAs ( Figure 2E , Tables S2 and S3 ).…”
Section: Resultssupporting
confidence: 69%
“…DNA topoisomerase 2-alpha ( TOP2A ), exodeoxyribonuclease 1 ( EXO1 ), serine/threonine-protein kinase Nek2 ( NEK2 ), baculoviral IAP repeat-containing protein 5 ( BIRC5 ), hyaluronan mediated motility receptor ( HMMR ), structural maintenance of chromosomes protein 4 ( SMC4 ), bloom syndrome protein ( BLM ), casein kinase I isoform epsilon ( CSNK1E ), cytoskeleton-associated protein 5 ( CKAP5 ), and inner centromere protein ( INCENP ) were identified as the hub genes based on the degrees of nodes which were more than 10 ( Figure 2 a) [ 11 ]. TOP2A , EXO1 , NEK2 , BIRC5 , SMC4 , BLM , CSNK1E , CKAP5 , and INCENP were related to DNA replication and cell division, and HMMR was related to cell motility [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The detailed functions of the hub genes are described in the discussion section and Supplementary Table S3 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, current reports have showed NEK2, as an important cyclin, has the functions of regulating the assembly and separation of centrosomes, the formation of spindles, and the precise separation of chromosomes [ 16 , 17 ]. In addition, NEK2 may also become an important marker for tumor differentiation and prognosis detection, and is an important potential target for cancer treatment [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite developments in clinical oncology technology, the prognosis for patients with LUAD is very poor 5 . Meanwhile, because of lack of effective biomarkers and not immediately apparent early symptoms, the clinical therapy available for LUAD is still disappointing 6,7 . Hence, it is essential that the progress of LUDA related gene expression and the molecular mechanism for early diagnosis and treatment is explored.…”
Section: Introductionmentioning
confidence: 99%